2017
DOI: 10.4172/2155-9554.1000431
|View full text |Cite
|
Sign up to set email alerts
|

Etiological Role of Ferritin and Vitamin D in Patients with Telogen Effluvium

Abstract: Introduction: Telogen effluvium (TE) is an abnormality of hair cycling that result in an abrupt onset of generalized shedding of telogen hairs from the scalp, with or without an entifiable trigger. Ferritin and vitamin D play an important role in hair follicle differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
2
1
Order By: Relevance
“…There was no significant association between occurrence of the disease and job or residency of the patients (P value =0.283 and 0.069, respectively; Table 2). Although, in current study, vitamin D level was significantly associated with duration and symptoms of telogen effluvium (P=0.046; Table 3), this finding was inconsistent with another study that suggested that there was no significant relation between level of vitamin D and duration of the disease (22,23). Vitamin D level among patients in acute phase was significantly higher than that among those with chronic phase (11.68±4.77ng/ml and 9.93±3.55ng/ml, respectively, P value=0.046; Table 3).…”
Section: Resultscontrasting
confidence: 98%
“…There was no significant association between occurrence of the disease and job or residency of the patients (P value =0.283 and 0.069, respectively; Table 2). Although, in current study, vitamin D level was significantly associated with duration and symptoms of telogen effluvium (P=0.046; Table 3), this finding was inconsistent with another study that suggested that there was no significant relation between level of vitamin D and duration of the disease (22,23). Vitamin D level among patients in acute phase was significantly higher than that among those with chronic phase (11.68±4.77ng/ml and 9.93±3.55ng/ml, respectively, P value=0.046; Table 3).…”
Section: Resultscontrasting
confidence: 98%
“…In all telogen effluvium patients, the hair pull test was positive all over the scalp (including frontal, 2 temporal and occipital regions). Also Telogen effluvium cases showed significantly higher vertex, occiput, right, left temporal, hair pull test when compared to control group Table (2).…”
Section: Results and Discussion 31 Clinical Resultsmentioning
confidence: 93%
“…Many mechanisms are impeded as severe fever, pregnancy, chronic systemic diseases, horrible hemorrhage, crash diet, sudden starvation, nutritional deficiency, accidental trauma, surgical operations and severe emotional stress. TE may be acute or chronic, if hair shedding lasts less than 6 months so it is acute TE, while chronic TE is hair shedding lasting longer than 6 months [2].…”
Section: Introductionmentioning
confidence: 99%